Transcriptomic, proteomic and ultrastructural studies on salinity-tolerant Aedes aegypti in the context of rising sea levels and arboviral disease epidemiology - Ranjan, R.; Thiruchenthooran, V.; Jayadas, T.T.P.; Eswaramohan, T.; Sharanga, S.; Kokila, S.; Naguleswaran, A.; Cayrol, M.U.B.; Voisin, S.N.; Bulet, P.; Surendran, S.N. (BMC Genomics, 2021)
Background: Aedes aegypti mosquito, the principal global vector of arboviral diseases, lays eggs and undergoes larval and pupal development to become adult mosquitoes in fresh water (FW). It has recently been observed to develop in coastal brackish water (BW) habitats of up to 50% sea water, and such salinity tolerance shown to be an inheritable trait. Genomics of salinity tolerance in Ae. aegypti has not been previously studied, but it is of fundamental biological interest and important for controlling arboviral diseases in the context of rising sea levels increasing coastal ground water salinity. Results: BW- and FW-Ae. aegypti were compared by RNA-seq analysis on the gut, anal papillae and rest of the carcass in fourth instar larvae (L4), proteomics of cuticles shed when L4 metamorphose into pupae, and transmission electron microscopy of cuticles in L4 and adults. Genes for specific cuticle proteins, signalling proteins, moulting hormone-related proteins, membrane transporters, enzymes involved in cuticle metabolism, and cytochrome P450 showed different mRNA levels in BW and FW L4 tissues. The salinity-tolerant Ae. aegypti were also characterized by altered L4 cuticle proteomics and changes in cuticle ultrastructure of L4 and adults. Conclusions: The findings provide new information on molecular and ultrastructural changes associated with salinity adaptation in FW mosquitoes. Changes in cuticles of larvae and adults of salinity-tolerant Ae. aegypti are expected to reduce the efficacy of insecticides used for controlling arboviral diseases. Expansion of coastal BW habitats and their neglect for control measures facilitates the spread of salinity-tolerant Ae. aegypti and genes for salinity tolerance. The transmission of arboviral diseases can therefore be amplified in multiple ways by salinity tolerant Ae. aegypti and requires appropriate mitigating measures. The findings in Ae. aegypti have attendant implications for the development of salinity tolerance in other fresh water mosquito vectors and the diseases they transmit.
Keywords: Aedes aegypti; Arboviral diseases; Climate change; Coastal salinity; Cuticle proteomics; Cuticle ultrastructure; Insecticide resistance; Rising sea levels; Transcriptomics; Salinity tolerance